Управління венчурними структурами в умовах невизначеності - Малиновський, Ю. В.; Кубрак, А. Б.; Мац, Ю. О.; Шендюк, Р. Б.; Malynovskyy, Yu. V.; Kubrak, A. B.; Mats, Yu. O.; Shendiuk, R. B. (Видавництво Львівської політехніки, 2023)
Дослідження розглядає проблему управління венчурними структурами в умовах невизначеності, де сучасні компанії стикаються з безпрецедентним рівнем змін та ризику. Актуальність дослідження зумовлена глобальними трансформаціями, геополітичними конфліктами, технологічними інноваціями та несподіваними змінами на ринках. Розглянуто стратегії управління венчурними структурами в умовах невизначеності, включаючи адаптацію до змін, диверсифікацію портфелю та залучення експертів. Також розглянуто роль технологічних інновацій у венчурному управлінні, включаючи їх вплив на ідентифікацію можливостей та автоматизацію процесів. Загальні висновки дослідження вказують на необхідність гнучких стратегій управління, використання сучасних технологій та розробку нових моделей інвестування для досягнення успіху в умовах постійної невизначеності та змін. Перспективи подальших досліджень включають аналіз впливу глобальних криз, регуляторних аспектів та психологічних факторів на венчурне управління, а також розширення співпраці між великими корпораціями та стартапами у цьому контексті.

The study examines the problem of managing venture structures in conditions of uncertainty, where modern companies face unprecedented change and risk. The relevance of the research is due to global transformations, geopolitical conflicts, technological innovations and unexpected market changes. The article discusses strategies for managing venture structures in conditions of uncertainty, including adaptation to changes, portfolio diversification, and involvement of experts. The role of technological innovations in venture management is also considered, including their impact on opportunity identification and process automation. Adaptive leadership is a crucial aspect of managing enterprises under conditions of uncertainty. This involves being flexible and responsive to the business’s changing environment and challenges. The study’s general conclusions indicate the need for flexible management strategies, the use of modern technologies and the development of new investment models to succeed in conditions of constant uncertainty and change. It is noted that the effective management of venture structures is essential for the country’s post-war recovery because it can become a catalyst for rapid economic recovery and stimulation of innovation. Venture capital contributes to the financing and development of innovative enterprises and technologies that can revolutionize various areas of the economy. This includes the development of new products, services and technologies that help solve social and economic problems. Creating a favorable ecosystem for venture capital can lead to the growth of innovative entrepreneurship and the attraction of important investments in promising industries. This, in turn, contributes to the creation of new jobs, the development of new technological industries and the restoration of economic potential after a period of conflict and war. An important advantage is also the ability of venture capital to attract foreign investments and contribute to the support of national innovative projects. This approach contributes to economic recovery and has a positive effect on the further development of the country. Prospects for further research include the analysis of the impact of global crises, regulatory aspects and psychological factors on venture management and the expansion of cooperation between large corporations and startups in this context.
The management of venture structures in conditions of uncertainty
Keywords: адаптивне лідерство; венчурні структури; невизначеність; ризик; стартапи; adaptive leadership; risk; startups; uncertainty; venture structures; 330.341.1; 334